Analysis of Land Use and Land Cover Changes in Ikot Abasi coastal Area from 1986-2016, Southern Nigeria, Using Landsat TM and ETM+ Images and GIS - Uko, Iberedem E.; Offiong, Raphael A. (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2021)
Ikot Abasi coastal area in Southern Nigeria, have witnessed enormous human activities which include commercial agriculture, industrial activities and urban development over the decades. Due to increasing land use in different dimensions the land cover in the area has been affected. This necessitated the gathering of land use and land cover statistically-based information which is the basis for monitoring and planning of sustainable coastal area management. This study was carried to quantitatively describe changes of land use and land cover in Ikot Abasi coast, Akwa Ibom State, from 1986 to 2016 using Landsat TM and ETM+ of the area, 1986 and 2013; and to carry out change detection in land cover between 1986-2016 in the study area. Image processing and change detection analysis were done through image interpretation processes using Erdas Imagine 9.2 software, and image Minus Algorithm of the mathematical Toolbox within ArcGIS 9.2 software respectively. Statistics indicated that out of 32,452.91ha area of land cover in 1986, the portion of land cover that has changed between 1986-2016 stood at 19,094.84ha (57.96%), while the portion of land cover that remain unchanged within that period was only 13,849.59ha (42.03%). With increasing human activities, more hectares of land cover are anticipated to be reduced in coming years. The study therefore, recommended sustainable agricultural practices such as bush fallowing, non-bush burning practice and selective tree cutting and implementation of development that is ecologically sustainable.